Understanding beverage taxation: Perspective on the Philadelphia Beverage Tax’s novel approach - Ryan M. Kane; Vasanti S. Malik (Journal of Public Health Research, 2019)
Despite the growing global trend of sugar-sweetened beverage (SSB) taxes for their potential as an untapped source of revenue and as a public health boon, these legislative efforts remain controversial. Multiple articles have reviewed this trend in recent years from modeling of long-term impacts to short-term empirical studies, yet most comprehensive, long-term health impact assessments remain forthcoming. These multi-faceted efficacy studies combined with case-based assessments of the policy process, descriptive pieces highlighting unique features of the policy and reflective perspectives targeting unanswered questions create a comprehensive body of literature to help inform present and future legislative efforts. The passage of the Philadelphia Beverage tax required a mix of political entrepreneurs, timing and context; while uniquely employing a nonpublic health frame, specific earmarking and a broadened scope with the inclusion of diet beverages. This perspective on the Philadelphia Beverage Tax will describe the passage and novel features of the Philadelphia Beverage Tax with a discussion of the ethical questions unique to this case.